Research on over-the-horizon air combat guidance method based on dynamic RCS - SONG Shaomei; YU Yifei; LI Gai; YANG Qiming; ZHANG Jiandong (Xibei Gongye Daxue Xuebao)
In order to solve the problem of target loss caused by too small target RCS in the process of long-range enemy contact, the relationship between target RCS and radar detection probability is analyzed, and a guidance method based on Particle Swarm Optimization (PSO) is proposed. Firstly, the influence of dynamic RCS is considered to obtain the optimal attack situation, and then the situation evaluation function considering dynamic RCS constraints is established. Then, to maximize the situation assessment value as the goal, particle swarm optimization algorithm is used to find the most appropriate overload at every moment, so as to guide our aircraft into the attack zone to constitute the launch conditions. The simulation results show that considering the RCS constraint, the particle swarm overload optimization method can reduce the fluctuation degree of target RCS and effectively reduce the probability of target loss during long-range enemy guidance.